Sócrates e a influência dos cultos de mistério no Êutifron - Melo, Luiz Fernando Bandeira de (2015)
Among the several thematic options found in the Platonic corpus, we decided to limit the scope of this research in the religiosity contained in the narrative that Plato develops about Socrates, in particular on the dialogue known as the Euthyphro youth. We will introduce as a highlight the influence of mystery cults that envolve the dialogue and the concern of the fortune-teller to defend himself from the curse caused by the crime committed by his father, which for such processes him in the Athenian court. The approach will present the comparison of points found in other Platonic dialogues, considered religious enough to demonstrate a new Socratic proposal to think the Greek man, in relation to their way of life. This innovation is in the transposition of the Orphic-Pythagorean Ideas, bringing a behavior that enables man\'s salvation from the penalty of repetitive transmigration of the soul after death of the body. The methodology of searching these points will still show the preservation of Socrates\' teachings as the Derveni papyrus was presented by its author. As a result of the research we intend to credit to Plato\'s máster, the innovation in the history of philosophy of a philosophical project of love of wisdom, expressed by the search for universal truths that are beyond human laws.